Preparation of 24 - hrs Sustained Release Tablets of Nicotinic Acid - Hue, Pham Thi Minh; Bach, Nguyen Van; Phommasone, Sonekeo (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2017)
Niacin (nicotinic acid) is a highly water-soluble vitamin, which has been used as a lipid-lowering agent. Sustained release (SR) niacin tablet was  developed in oder to maintain a constant drug concentration for a specific period of time with minimum side effects . In this study, the once daily extended release matrix tablets of niacin using a hydrophilic polymer of HPMC K100M as matrix excipient were prepared by wet granulation method. The results of the dissolution study indicated that the release of the drug was found to be dependent on the proportions of HPMC used in the tablets. The dissolution profile of the optimal formula was similar to that of the predict and attained the requirements of USP 37. The dug incorporated in the matrix released by diffusion and fitted the first order kinetic. Keyword Niacin, sustained release, hydrophilic matrix, HPMC References [1] Bộ Y tế, Dược điển Việt Nam IV, NXB Y học, 2009. [2] Harol E. Bays, Carlos A. Dujovne, (2003), “Comparison of one - daily, Niacin extended-release/ Lovastatin with Standard doses of Atorvastatin and Simvastatin (The advicor Versus othe cholesterol-Modulating Agents Trial Evaluation)”, Am J Cardiol., 91, pp. 667-672. [3] Juergen Siepmann, F. Siepmann (2008), “Mathematical modeling of drug delivery”, International Journal of Pharmaceutics, 364, pp. 328-343. [4] Patel D.N., Ghelani T.K. (2011), “Formulation and evaluation of once daily niacin extended release matrix tablets”, Pharma Science Monitor, 2(4), pp.145-153. [5] Rezowanur Rahman, Sheikh Tasnim Jahan (2010), “Preparation and evaluation of mucoadhesive hydrophilic hydroxy propyl methyl cellulose based extended release matrix tablets of Niacin (Nicotinic acid)”, American Journal of Scientific and Industrial Research, pp. 558-564. [6] Paulo Costa, José Manuel Sousa Lobo (2001), “Modeling and comparison of dissolution profiles”, European Journal of Pharmaceutical Sciences, 13, pp. 123-133. [7] USP 37, pp. 3980-3981.